The Effect of Inhaler Training on Self-Efficacy among Patients with COPD - Hasby Pri Choiruna; Ratna Sitorus; I Made Kariasa (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Patients with Chronic Obstructive Pulmonary Disease (COPD) can have low self-efficacy due to symptoms of shortness of breath and cough. Proper use of an inhaler is able to overcome these symptoms. The majority of COPD patients are still using inhalers incorrectly. Inhaler use training can improve the technique of inhaler use and is expected to improve self-efficacy in COPD patients. The purpose of this study was to determine the effect of inhaler training on self-efficacy in COPD patients. The research design used a quasi-experiment with a nonequivalent control group pretest-postest. Thirty-six patients with COPD were selected using consecutive sampling and were divided into groups that followed the inhaler training and those who did not follow the inhaler training. The results showed that there was a significant improvement in self-efficacy in COPD patients by 9.33 score after the inhaler training (p=0.001; p<0.05) and there was a significant difference in self-efficacy change of 6 scores compared to COPD patients who did not follow the inhaler training (p=0.000; p<0.05). In conclusion, there was an influence of inhaler training on self-efficacy in COPD patients so inhaler training is recommended to that nurses to be given to COPD patients.